In vitro antimicrobial activity and characterization of mangrove isolates of streptomycetes effective against bacteria and fungi of nosocomial origin - Das,Arijit (2014)
The study aimed at determining the in vitro antimicrobial activity of alkaliphilic and halotolerant actinomycetes isolated from a mangrove ecosystem and identification of a potent strain. Twenty five isolates of actinomycetes were isolated from the sediment samples of Valapattanam mangrove swamp in Kerala, India. Antimicrobial activity of four selected actinomycete isolates was determined against bacterial and fungal pathogens of nosocomial origin by agar well diffusion method. Molecular characterization of the potent isolate was performed by 16S rDNA sequencing. Isolate no I-1 significantly inhibited Staphylococcus aureus ATCC 25923 (12 mm), S. aureus (15±0.05 mm), S. citreus (20±0.5 mm), Bacillus cereus (17±0.2 mm) and Serratia marcescens (12 mm). It also demonstrated effective antifungal action against Penicillium sp. (12±0.2 mm), Candida albicans (20±0.5 mm), C. parapsilosis (12 mm) and Cryptococcus neoformans (12 mm). Morphological study revealed that all the isolated actinomycetes belonged to the genus Streptomyces. Based on 16S rDNA sequence data, the selected isolate I-1 was shown to be closely related to Streptomyces xiamenensis. The results revealed that the mangrove ecosystem of Valapattanam harboured a rich consortium of many potent actinomycetes, which could synthesize novel bioactive compounds of pharmacological significance.